Color weakness in congenital color perception deficiency of various degrees - A.V. Ponomarchuk; N.I. Khramenko (Ukrainian Society of Ophthalmologists, 2018)
Background: The prevalence of congenital color vision defects (CCVD) is reported to be approximately 8% in males and 0.5% in females, and, therefore, the use of optimal tests capable of diagnosing these defects early and accurately, and with all the aspects of color perception deficiency addressed, is important. Purpose: To investigate color weakness in protans and deutans with congenital color vision defects varying in severity. Materials and Methods: The Yustova threshold plates were used to assess color discrimination thresholds in two groups, the protans (253 individuals) and the deutans (374 individuals). The former group included type A, type B, and type C protanomals (61, 49, and 64 individuals, respectively) and 79 protanopes, whereas the latter group included type A, type B, and type C deuteranomals (34, 124, and 127 individuals, respectively) and 89 deuteranopes. At baseline, patients underwent visual acuity assessment (using the Shevalev charts and Golovin-Sivtsev charts), refractometry, biomicroscopy and ophthalmoscopy. Patients were emmetropes, had the visual acuity of 1.0 in either eye, and had neither ocular nor systemic disease. Results: A colorimetric methodology revealed the features of color discrimination thresholds of the R receptor in protans, with mild to moderate red weakness in 31% of the type C protanomals, 85.6% of the type B protanomals, 70.3% of the type A protanomals, and with moderate to severe red weakness in 100% of the protanopes. A mild green weakness was found in 23.7% of the protans with any degree of color anomaly. Of the deutans, 51.8% exhibited a mild red weakness. In addition, 19.6% of the type C deuteranomals exhibited a mild green weakness, 55.5% of the type B deuteranomals exhibited mild to moderate green weakness, and 85.3% of the type A deuteranomals exhibited mild to moderate green weakness. Moreover, a green weakness of any degree was found in all the deuteranopes, with 51.9% of them exhibiting a severe green weakness. Conclusion: Congenital color vision defects are characterized not only by impaired spectral color perception, but also by apparent color weakness.